Diversidad florística de los petenes de Campeche - Duran Garcia, Rafael (Instituto de Ecología, A.C., 1995)
The use of several indices and theoretical models for the study of floristic diversity, species abundance and species richness is discussed. These descriptive methods are applied to four patches of tropical vegetation known as hammocks or “petenes” in NW Campeche state, Mexico. It is suggested that the Hill index best indicates vegetation diversity. The results show that dominance decreases as island size and diversity increase. The distributions of species abundance conform to Motomura’s model, suggesting that these communities represent different successional stages.